The Effectiveness of Teaching Nursing Ethics via Scenarios and Group Discussion in Nurses’ Adherence to Ethical Codes and Patients’ Satisfaction with Nurses’ Performance - Fatemeh Izadi; Mostafa Bijani; Zhila Fereidouni; Shahnaz Karimi; Banafsheh Tehranineshat; Azizallah Dehghan (The Scientific World Journal)
Background. There are shortcomings in nurses’ adherence to ethical principles in practice. The present study aims to investigate the effectiveness of teaching nursing ethics via scenario-based learning and group discussion in nurses’ adherence to codes of ethics and patients’ satisfaction with nurses’ performance. Methods. Using a quasiexperimental design, the present study employed questionnaires which measure nurses’ compliance with nursing codes of ethics and patients’ satisfaction with nursing care before, immediately after, and one month after intervention. The collected data were analyzed using the independent t-test, ANOVA, and chi-square test in SPSS v.22. The level of significance was set at p<0.05. The nurses (n = 80) and patients (n = 160) from various units of two university hospitals in the south-west of Iran participated in the present study. Results. The pretest mean scores of the intervention and control groups in patient rights and patients’ satisfaction with nursing care were not significantly different (p=0.07, p=0.21). Yet, there were statistically significant differences between the groups’ mean scores as calculated immediately after (p<0.001, p<0.001) and one month after intervention (p<0.001, p<0.001). Conclusion. Employment of new approaches to teach nursing ethical principles improves compliance with nursing ethical codes and patients’ satisfaction with nurses’ performance.